An Investigation of Materialism and Life Satisfaction - Faiza, Afreen (Universitas Ahmad Dahlan, 2017)
Abstract The collectivistic culture of Pakistan is perforating with hedonic, modern and lavishing values. People are becoming more concerned with material aspirations and accumulation of wealth. The aim of present study is to investigate the relationship between materialism and life satisfaction among Pakistani individuals. A sample of (N=104) Muslim individuals were recruited through random sampling technique from different areas of Karachi city. Their age ranged from 16-46 years (M= 1.60, S.D=.854). The individuals were administered Richins Material values scale (2004) and Diener et al. [G1] the Satisfaction with Life Scale (1985). A significant positive relationship was obtained between materialism and life satisfaction (r=.273, p< .01). The future implementation of strategies for promotion of wellbeing of Pakistani individuals is discussed in the light of findings of present study.Keywords: Materialism, Life Satisfaction, Muslim, Karachi, Pakistan